1997
DOI: 10.3147/jsfp.32.153
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro immunostimulation of turbot(Scophthalmus maximus) leucycytes with .BETA. glucan and/or Photobacterium damsela bacterin.

Abstract: Respiratory burst and phagocytic activities of turbot (Scophthalmus maximus) leucocytes were determined after an in vitro incubation of head kidneys with different doses of yeast glucan and Photobacterium damsela (formerly Vibrio damsela) O-antigen.Although there was an increment of these immune functions with the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Other studies have also demonstrated that in vitro application of -glucans induce superoxide production in macrophages from a number of fish species including Atlantic salmon (S. salar) (Dalmo & Seljelid, 1995;Jorgensen & Robertsen, 1995), rainbow trout (O. mykiss) (Novoa et al, 1996), dab (Limanda limanda) (Tahir & Secombes, 1996), turbot (S. maximus) (Figueras et al, 1997) (P. maxima) (Castro et al, 1999) and gilthead seabream (S. auratus) (Castro et al, 1999). Therefore, it is not surprising that EcoActiva was able to directly induce respiratory burst of snapper (P. auratus) macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also demonstrated that in vitro application of -glucans induce superoxide production in macrophages from a number of fish species including Atlantic salmon (S. salar) (Dalmo & Seljelid, 1995;Jorgensen & Robertsen, 1995), rainbow trout (O. mykiss) (Novoa et al, 1996), dab (Limanda limanda) (Tahir & Secombes, 1996), turbot (S. maximus) (Figueras et al, 1997) (P. maxima) (Castro et al, 1999) and gilthead seabream (S. auratus) (Castro et al, 1999). Therefore, it is not surprising that EcoActiva was able to directly induce respiratory burst of snapper (P. auratus) macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…This process has been referred to as the respiratory or oxidative burst (Secombes & Fletcher, 1992). Studies have shown that culturing isolated macrophages in vitro with -glucan preparations can modulate the respiratory burst activity of these cells from many fish species including rainbow trout (Oncorhynchus mykiss) (Jorgensen et al, 1993), Atlantic salmon (Salmo salar) (Jorgensen & Robertsen, 1995), turbot (Scophthalmus maximus) (Figueras et al, 1997) (Psetta maxima) (Castro et al, 1999) and gilthead seabream (Sparus auratus) (Castro et al, 1999). These studies have also been able to di#erentiate the e#ects of -glucan administration into either direct stimulatory e#ects or into priming e#ects that enhance respiratory burst, following subsequent stimulation (Jorgensen & Robertsen, 1995;Tahir & Secombes, 1996;Castro et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast M-glucan, the compound used in the present study, is well known for its immunomodulatory properties in fish and fish cell lines. Previous work has demonstrated that optimum immunostimulatory effects are attained by administration of intermediate doses in vitro (0.1e1 mg/ml [32]; 10e50 mg/ml [28]) and in vivo (40 mg/fish) [39]. As a consequence, only an intermediate dose (50 mg glucan/fish) was chosen for our study.…”
Section: Microbial Polymers Such As Lps and Yeast Glucans Do Not Stimmentioning
confidence: 98%
“…Different fungal derived compounds especially the cell wall polymers made of b-1,3 and b-1,6 linkages known as glucans have been shown to increase innate immune responses of fish such as elevated phagocytic activity [28], lysozyme activity [29e30], macrophage activation [31e32], adjuvanticity [33] and bacterial disease resistance [34e36]. However, neither yeast compounds nor Vibrio vaccines have been previously investigated for their interferon/Mx inducing properties in fish.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the extensive use of broad-spectrum antibiotics in aquaculture has led, as in other fields, to drug resistance problems (32). In order to improve health and welfare in the rearing of these animals, several alternatives such as improved husbandry, nutrition, and water quality; lower stocking densities; and use of vaccines, nonspecific immunostimulants (7), and bacterial probiotics such as lactic acid bacteria (LAB) (9,26) have been proposed.…”
mentioning
confidence: 99%